2021
DOI: 10.3390/ijerph182312856
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, Mood States, and Choking in Asian University Baseball Players under Pressure during a Game

Abstract: The purpose of this study was to investigate relationships among mood states, perfectionism, and choking, and to identify a mediating effect of perfectionism on the relationship between mood states and choking experienced by Asian university baseball players in extremely stressful situations during a game. Data collected from a total of 209 male university baseball players were analyzed using SPSS 21 and AMOS 21 statistical software. The mean age of study subjects was 20.25 years. Results are as follows. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 44 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…In addition, the primary conflict in the inconsistent research results is that changes in mood states do not necessarily lead to a change in performance. However, Yoon et al [4] identified that changes in mood states that occur in the presence of perfectionism become an indirect variable that causes choking, which supports the inference that certain factors mediate in the influence relationship between changes in mood states and perceived performance. We believe it is necessary to study these mediating factors, and that is the objective of this study.…”
Section: The Relationships Between Mood States Competitive State Anxi...mentioning
confidence: 90%
See 4 more Smart Citations
“…In addition, the primary conflict in the inconsistent research results is that changes in mood states do not necessarily lead to a change in performance. However, Yoon et al [4] identified that changes in mood states that occur in the presence of perfectionism become an indirect variable that causes choking, which supports the inference that certain factors mediate in the influence relationship between changes in mood states and perceived performance. We believe it is necessary to study these mediating factors, and that is the objective of this study.…”
Section: The Relationships Between Mood States Competitive State Anxi...mentioning
confidence: 90%
“…To help subjects fully understand the term "choking under pressure situations (extremely stressful situations [4])", we spent the first 10 minutes of each survey session defining the concept for the players before they completed their questionnaires. The most common definition suggests that choking is "a sudden decrease in the execution of skill and performance considerably when athletes believe that they can not meet standards set by themselves.…”
Section: Choking Under Pressure Situationsmentioning
confidence: 99%
See 3 more Smart Citations